Grodno – a City of Culture of Many Confessions - Tovmasyan, Eduard (project baikal, 2014)
The article deals with the history and architecture of the Belarusian city of Grodno, one of the ancient cities built up at the intersection of diverse cultures. It provides extensive historical materials on the city and its most outstanding buildings. The author’s personal impressions and photos enliven the text.